2019
DOI: 10.1080/00140139.2019.1566579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physiological workload assessment methods using heart rate and accelerometry for a smart wearable system

Abstract: Work metabolism (WM) can be accurately estimated by oxygen consumption (VO 2 ), which is commonly assessed by heart rate (HR) in field studies. However, the VO 2 -HR relationship is influenced by individual capacity and activity characteristics. The purpose of this study was to evaluate three models for estimating WM compared with indirect calorimetry, during simulated work activities. The techniques were: the HR-Flex model; HR branched model, combining HR with hipworn accelerometers (ACC); and HR þ arm-leg AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 51 publications
(69 reference statements)
0
15
0
1
Order By: Relevance
“…As such, walking speed is considered an additional vital sign of health [ 2 ] and represents an appropriate mobility measure for multiple populations. This is mirrored by strong evidence that mobility outcomes, such as walking speed and duration, predict mortality, falls, cognitive impairment, disability and other clinical outcomes [ 3 , 4 , 5 , 6 , 7 ]. As new therapies place more and more focus on multimorbid elders and on improving their quality of life and independence, the importance of assessing how a new medical product impacts mobility is growing exponentially.…”
Section: Introductionmentioning
confidence: 99%
“…As such, walking speed is considered an additional vital sign of health [ 2 ] and represents an appropriate mobility measure for multiple populations. This is mirrored by strong evidence that mobility outcomes, such as walking speed and duration, predict mortality, falls, cognitive impairment, disability and other clinical outcomes [ 3 , 4 , 5 , 6 , 7 ]. As new therapies place more and more focus on multimorbid elders and on improving their quality of life and independence, the importance of assessing how a new medical product impacts mobility is growing exponentially.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous observation of exercise intensity may enable the accurate estimation of energy expenditure (EE), which would also make the nutrition control more precise. Although previous studies have reported limitations in estimation of EE with wearable devices [4042], the combination of HR measurement with accelerometry may improve the accuracy of EE estimation with the wearable devices [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Metode denyut nadi atau disebut juga dengan metode Cardiovascular Load (CVL) merupakannsalah satu metode tidak langsung yang dapat mengukur beban kerja fisiologis. Denyut nadi juga dipengaruhi oleh faktorfaktor lain, seperti stres, asupan makanan dan kondisi lingkungan [11]. Pengukuran denyut jantung dapat dilakukan dengan berbagai cara yaitu: 1.Merasakan denyut jantung yang ada pada arteri radial pada pergelangan tangan.…”
Section: Metode Cvlunclassified